Parents' advice to healthcare professionals working with children who have spinal muscular atrophy. (January 2018) - Hjorth, Elin; Kreicbergs, Ulrika; Sejersen, Thomas; Lövgren, Malin
Abstract: Aim: To explore parents' advice to healthcare professionals working with children with spinal muscular atrophy (SMA). Materials and methods: This study derives from a Swedish nationwide survey and uses content analysis to make inferences from answers to an open-ended question concerning parent's advice to healthcare professionals. Of eligible parents who had a child born in Sweden between 2000 and 2010, diagnosed with SMA type 1 or 2, and for whom respiratory support was considered in the first year of life, 61 participated in the study (response rate: 87%). Of these, 51 parents answered the question about advice to healthcare professionals working with children with SMA. Results: More than half of the advice from parents was related to professional–family relations. The second most frequent type of advice related to two aspects of knowledge about SMA: desire that healthcare professionals possess knowledge, and desire that they provide knowledge. The parents also had advice concerning support in daily life, both to the parents and to the affected child. Other pieces of advice were related to organization of care and the parents' desire to be involved in the child's care. Conclusions: Parents advised healthcare professionals to increase their disease-specific knowledge, to treat the parents as experts on their child, and to treat the family with respect, particularly in situations where the child's case is used as an opportunity to improve healthcare professionals' competence. Increased practical support in daily life and a case coordinator is also among parents' advice to healthcare professionals. Highlights: Parents want healthcare staff to be more knowledgeable about SMA. Parents want staff to provide them with information and be receptive to their views. Parents suggest organizational changes to improve practical support for families.